2016
DOI: 10.3390/ijerph13060571
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Community Readiness to Reduce Childhood Diarrheal Disease and Improve Food Security in Dioro, Mali

Abstract: Diarrhea and malnutrition represent leading causes of death for children in Mali. Understanding a community’s needs and ideas are critical to ensure the success of prevention and treatment interventions for diarrheal disease, as well as to improve food security to help reduce malnutrition. The objective of this study was to incorporate the Community Readiness Model (CRM) for the issues of childhood diarrheal disease and food security in Mali to measure baseline community readiness prior to any program implemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…The CRM has been utilized largely in high-income countries to assess community readiness of a number of different issues in public health, including obesity (Kesten et al, 2013;Kostadinov et al, 2015). Some CRM studies have also been undertaken in Low and Middle Income Countries (LMICs), examining childhood diarrhea in Mali (Borresen et al, 2016), healthy diets among adolescents girls and women Ghana (Pradeilles et al, 2019), and adolescent obesity in South Africa (Pradeilles et al, 2016).…”
Section: Methodsmentioning
confidence: 99%
“…The CRM has been utilized largely in high-income countries to assess community readiness of a number of different issues in public health, including obesity (Kesten et al, 2013;Kostadinov et al, 2015). Some CRM studies have also been undertaken in Low and Middle Income Countries (LMICs), examining childhood diarrhea in Mali (Borresen et al, 2016), healthy diets among adolescents girls and women Ghana (Pradeilles et al, 2019), and adolescent obesity in South Africa (Pradeilles et al, 2016).…”
Section: Methodsmentioning
confidence: 99%
“…Limited research has been conducted in low- and middle-income countries (LMICs) using the CRM. For example, it has been applied to preventing communicable diseases in Bangladesh [22] and Mali [23], and mental health stigma in Vietnam [24]. Only one study (from South Africa) has assessed community readiness for overweight/obesity prevention in Africa [25].…”
Section: Introductionmentioning
confidence: 99%
“…A similar CRM to identify readiness to address childhood diarrheal disease and food security issues in Dioro, Mali was applied. Here, they found that there was community enthusiasm around the incorporation of additional ingredients to traditional foods to improve nutrition and health [20]. Since this initial CRM assessment in Mali, an effective dietary intervention study was held in this community to prevent childhood malnutrition and decrease diarrhea incidence [32].…”
Section: Discussionmentioning
confidence: 99%
“…The CRM is designed to assess a community's degree of readiness to address a specific issue. This tool has been essential in the successful development and implementation of programs related to a wide range of topics [17][18][19][20][21]. The objective of this study was to apply the CRM to assess current awareness and readiness to address the complex issues of childhood malnutrition in a rural region of southwest Guatemala that suffers from high rates of food insecurity and childhood malnutrition [22,23].…”
Section: Introductionmentioning
confidence: 99%